2018
DOI: 10.1021/acs.cgd.8b00768
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosynthesis of Nanocrystalline Fully Stabilized bcc γ-phase of Bi2O3 without Any Additive: Manifestation of Ferroelasticity in Microstructure, Optical, and Transport Properties

Abstract: In the present work, polymorphic phase transformation of Bi2O3 nanoparticles by the mechanical alloying method has been investigated in detail. X-ray diffraction study reveals that the room temperature stable monoclinic α-phase of Bi2O3 can be stabilized into body-centered cubic γ-phase by applying mechanical energy only to the Bi2O3 powder, without adding any dopant to the Bi2O3 matrix. The crystallite size of the γ-phase is reduced up to ∼24 nm after 18 h of milling the analytical grade α-Bi2O3 powder. Optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…In β-phase the coordination about the Bi atom is four folds and the coordination polyhedron is described by a distorted trigonal bipyramid in which one of the basal corners is occupied by the electron pair 20 . In accordance with the literature data, the monoclinic α-phase exhibits transition to the face centered cubic δ-phase by heating the compound at 730 o C 21 . It is mentioned that owing to the large thermal hysteresis during the natural cooling cycle, δ-phase transform to tetragonal β-phase (usually stabilize at 650 ºC) and to body centered cubic (bcc) γ-phase.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In β-phase the coordination about the Bi atom is four folds and the coordination polyhedron is described by a distorted trigonal bipyramid in which one of the basal corners is occupied by the electron pair 20 . In accordance with the literature data, the monoclinic α-phase exhibits transition to the face centered cubic δ-phase by heating the compound at 730 o C 21 . It is mentioned that owing to the large thermal hysteresis during the natural cooling cycle, δ-phase transform to tetragonal β-phase (usually stabilize at 650 ºC) and to body centered cubic (bcc) γ-phase.…”
Section: Resultssupporting
confidence: 90%
“…The bcc phases result from controlled cooling of δ phase. Both of the β-and δ phases convert to the monoclinic phase in the temperature range of 500-650 o C 21 . In our previous investigation 13 we have reported that the Bi 2 O 3 thin films which are deposited onto Yb substrate exhibit body centered cubic γ-phase.…”
Section: Resultsmentioning
confidence: 99%
“…Annealing of Bi NPs in the air leads to the formation of bismuth oxides, which can be described as [ 37 , 38 ]. This route is very simple, cost-effective, and also free from any additional chemicals such as surfactants and template agents, which could introduce impurities as a byproduct [ 24 , 33 ]. Therefore, in this study, the synthesis of γ‒Bi 2 O 3 NPs was carried out in two steps.…”
Section: Methodsmentioning
confidence: 99%
“…method plays a significant role in defining the size and the structural properties [33]. The fitted value of occupancy at the Bi(1), O(1), and O(3) sites remains very close to 1, whereas the occupancies at the Bi(2) and O(2) sites are 0.943 (8) and 0.861 (29), respectively.…”
Section: Structural Propertiesmentioning
confidence: 98%
See 1 more Smart Citation